Cytotoxicity of Ganciclovir on Cultured Human Corneal Endothelial Cells. Issue 6 (August 2013) - Choi, Won Seok; Koh, Jae Woong; Chung, Tae Young; Hyon, Joon Young; Wee, Won Ryang; Shin, Young Joo
Background: Intraocular cytomegalovirus (CMV) infections, including endotheliitis and retinitis, have been reported to threaten the host's vision. These infections have been treated with systemic or intravitreal GCV injection. Intracameral GCV injection can be an effective treatment option that avoids systemic side effects. The cytotoxic effect of ganciclovir (GCV) on cultured human corneal endothelial cells (HCECs) was evaluated. Methods: HCECs were cultured and exposed to various concentrations (0–20 mg/ml) of GCV (Cytovene®). Cell viability was assessed by the Cell Counting Kit-8 method and live/dead viability/cytotoxicity assays. Cell morphology was assessed using phase-contrast microscopy after 48 h exposure to GCV. Cell cycle and apoptosis were analysed using NC-3000 to evaluate the effect of GCV on HCECs. The cell proliferation rate was evaluated by a bromodeoxyuridine proliferation assay. Results: Cytotoxicity tests showed that GCV had a dose-dependent cytotoxic effect on HCECs. GCV concentrations of ≥5 mg/ml resulted in a significant reduction in cell viability. Higher concentrations of GCV resulted in cell cycle delay, low proliferation rate, and an increased number of apoptotic cells, indicating activation of the pro-apoptotic pathway. Conclusions: Our results suggest that intracameral GCV concentrations of ≥5 mg/ml may increase the risk of corneal endothelial damage, although GCV concentrations of ≤0.5 mg/ml do not decrease cell viability.